2005
DOI: 10.1007/bf02849888
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-lowering effect of 2 dosages of a soy protein supplement in Hypercholesterolemia

Abstract: The lipid-lowering effect of a soy-based protein supplement was evaluated in an 8-week randomized, placebo-controlled trial in patients with hypercholesterolemia. A total of 117 patients (63 men and 54 women) received soy protein, either 15 or 25 g/d or placebo. In the active treatment groups low-density lipoprotein cholesterol levels decreased significantly by 5.9% and 1.1% respectively, but increased by 3.6% with placebo. Total serum cholesterol and apolipoprotein B levels changed significantly in a similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Our search identified 3917 reports, of which 3689 were excluded on the basis of review of titles and abstracts. The remaining 228 articles were reviewed in full, of which 104 provided data for 112 trial comparisons for inclusion in our analyses …”
Section: Resultsmentioning
confidence: 99%
“…Our search identified 3917 reports, of which 3689 were excluded on the basis of review of titles and abstracts. The remaining 228 articles were reviewed in full, of which 104 provided data for 112 trial comparisons for inclusion in our analyses …”
Section: Resultsmentioning
confidence: 99%
“…Both soy-nut and soy-protein had beneficial effects on serum concentrations of total cholesterol, LDL cholesterol, triacylglycerol, and apoB-100. Such results have also been seen among subjects with different types of diseases (Hoie et al, 2005). Beneficial effects of soy consumption on blood lipids were the most consistently reported findings (Hermansen et al, 2005).…”
Section: Accepted Manuscriptmentioning
confidence: 78%
“…The American Heart Association recognizes that eating soy protein can help decrease LDL-c levels by two to seven percent [34,35]. In an another study, it was reported that soy protein decreased LDL-c levels five to six percent [36].…”
Section: Human Studiesmentioning
confidence: 99%